Analysis of education promotion at Aisyiyah Lampung Kindergarten - Suyarti, Sri; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi; Patimah, Siti (Goodwood Publishing, 2024)
Purpose: This research delves deeply into various strategic aspects involving Aisyiyah Lampung Kindergarten, a preschool educational institution in Lampung. The main focus of the research involves the analysis of common problems related to education promotion, with an in-depth focus on promotion strategies, branding, local community involvement, and educational excellence. Results: The results of the study show that the main problems of institutions involve promotional strategies that need to be updated, as well as the challenge of building a strong brand image. Improvement efforts, such as increased involvement in the local community, clarification of promotional messages, and emphasis on the institution's core values, have had a positive impact on the brand image of Aisyiyah Lampung Kindergarten. These results have implications that a holistic strategy involving active engagement, careful brand management, and a focus on educational excellence can increase the institution's attractiveness in the eyes of the local community. Contribution: This research contributes to a further understanding of the dynamics of preschool education and provides a foundation for continuous improvement in brand promotion and management strategies in similar institutions.